Work-related musculoskeletal disorders among nurses at the Georgetown Public Hospital Corporation in Guyana - Punch, Noelhi Hermes (2021)
Nurses are affected by work-related musculoskeletal disorders (WMSD), which are related to the work activities performed during nursing practice. Therefore, the purpose of this quantitative, descriptive, cross-sectional study was to investigate the occurrence of work-related musculoskeletal disorders among Registered Nurses (RN) and Nursing Assistants (NA) working at the Georgetown Public Hospital Corporation (GPHC), Guyana. A total of 271 nurses (185 RN and 86 NA) participated in the study, and data collection was performed using an instrument to the characterization of the nurses and the Nordic Musculoskeletal Questionnaire (NMQ). The Integrated Model of WMSD was used as the theoretical framework of this research. The study findings revealed that female nurses were more affected by WMSD than male nurses, and the younger nurses with shorter years of experience were the most affected by WMSD. Also, most of the nurses were of African descent, single, had children, and had a diploma in nursing as their highest level of education. The prevalence of WMSD over the last 12 months was 91.5% among the RN and NA, most of the RN (63.1%) and NA (28.4%) reported WMSD, and 28.0% of the nurses reported sick or absent from work, but only 25.1% of the nurses visited a physician because of the problem. More so, 55.0% of the study participants reported body mechanics ergonomics (BME) training, and 82.3% of the nurses accepted that they need BME training. The most commonly affected body region in the last 12 months was the lower back (72.0%), followed by the neck (49.1%), shoulders (37.7%), legs (37.6%), wrist/hands (33.9%), knees (33.2%), upper back (32.5%), hips/buttocks (18.5%), and elbows (4.8%). Also, the most commonly affected site in the last week was the lower back (50.2%), followed by the neck (27.3%), legs (26.2%), upper back (23.2%), shoulders (20.3%), knees (19.2%), wrist/hands (18.8%), hips/buttocks (11.1%), and elbows (3.7%), and there was a significant decrease in the prevalence of WMSD among the nurses in the last week compared to the last 12 months. Most of the nurses were unable to carry out relaxation activities in the last 12 months because of musculoskeletal pain in all nine regions of their bodies. Lower back pain was most prevalent among the nurses working in the Medical/Surgical Units (35.1%), Emergency and Intensive Care Units (22.9%), and Pediatric Units (10.7%). Statistically significant associations (at the 0.05 significant level) were found between sex and WMSD in the last 12 months for the upper back and one/both legs, sex and job demands and social support in the last 12 months and last week. Also, significant associations were found between age and WMSD in the last 12 months for the hips/buttocks region of the body, and between nursing category and WMSD in the last 12 months for the neck region. More so, statistically significant associations were found between ward and WMSD in the last 12 months and last week for the neck, lower back, and shoulders, between education level and WMSD in the last 12 months in the neck, in one/both knees, and one/both legs, and between years of employment and WMSD in the last 12 months and last week in one/both legs. Therefore, we concluded that there was a high prevalence of WMSD among the nurses at the GPHC, and lower back pain was the most common type of WMSD. Therefore, more research is needed to develop health promotion programs at work in the GPHC.